Feasibility of Protective Ventilation During Elective Supratentorial Neurosurgery: A Randomized, Crossover, Clinical Trial. Issue 3 (July 2018) - Ruggieri, Francesco; Beretta, Luigi; Corno, Laura; Testa, Valentina; Martino, Enrico A.; Gemma, Marco
Abstract : Background: Traditional ventilation approaches, providing high tidal volumes ( V t ), produce excessive alveolar distention and lung injury. Protective ventilation, employing lower V t and positive end-expiratory pressure (PEEP), is an attractive alternative also for neuroanesthesia, when prolonged mechanical ventilation is needed. Nevertheless, protective ventilation during intracranial surgery may exert dangerous effects on intracranial pressure (ICP). We tested the feasibility of a protective ventilation strategy in neurosurgery. Materials and Methods: Our monocentric, double-blind, 1:1 randomized, 2×2 crossover study aimed at studying the effect size and variability of ICP in patients undergoing elective supratentorial brain tumor removal and alternatively ventilated with V t 9 mL/kg—PEEP 0 mm Hg and V t 7 mL/kg—PEEP 5 mm Hg. Respiratory rate was adjusted to maintain comparable end-tidal carbon dioxide between ventilation modes. ICP was measured through a subdural catheter inserted before dural opening. Results: Forty patients were enrolled; 8 (15%) were excluded after enrollment. ICP did not differ between traditional and protective ventilation (11.28±5.37, 11 [7 to 14.5] vs. 11.90±5.86, 11 [8 to 15] mm Hg; P =0.541). End-tidal carbon dioxide (28.91±2.28, 29 [28 to 30] vs. 28.00±2.17, 28 [27 to 29] mm Hg; P <0.001). Peak airway pressure (17.25±1.97, 17 [16 to 18.5] vs. 15.81±2.87, 15.5 [14 to 17] mm Hg; P <0.001) and plateau airway pressure (16.06±2.30, 16 [14.5 to 17] vs. 14.19±2.82, 14 [12.5 to 16] mm Hg; P <0.001) were higher during protective ventilation. Blood pressure, heart rate, and body temperature did not differ between ventilation modes. Dural tension was "acceptable for surgery" in all cases. ICP differences between ventilation modes were not affected by ICP values under traditional ventilation (coefficient=0.067; 95% confidence interval, −0.278 to 0.144; P =0.523). Conclusions: Protective ventilation is a feasible alternative to traditional ventilation during elective neurosurgery. Abstract : Supplemental Digital Content is available in the text.